(untitled) (Journal of Bangladesh Institute of Planners, 2013)
Sustainable city with sustainable transportation system in now become the heartiest demand for burgher, especially in a city like Dhaka; where ecological imbalance lead to unbearable livable condition with unsustainable growth in every sector resulting the degradation of life quality. Transportation sector in Dhaka is one of the major adherents behind ecological deterioration by emitting enormous CO2 in atmosphere. Thus this study aimed at determining the transport footprint for vehicles travel in Dhaka. The study estimates the CO2 emission from motorized vehicles using average emission factor method and then determines the average bio-capacity of Dhaka city to compare it with the footprint. The study finds out that only for vehicles CO2 emission and physical transportation network; the transport footprint is seventy times larger than the bio-capacity. In transportation sector of Dhaka; ecological footprint credibly depicts the present condition, that is not at all sustainable from environmental friendly transport system context and it also an absolute indication for future concerning transport development pattern and their holes. At this point for developing sustainable transportation system considering ecological balance; Transport Demand Management (TDM), low carbon transport, transit oriented development (TOD), and creation of green corridors can be of some greatest tools for Dhaka. Journal of Bangladesh Institute of Planners, Vol. 6, Dec 2013, pp. 137-147